A REVIEW ON THE PHARMACOLOGICAL AND TRADITIONAL PROPERTIES OF MIMOSA PUDICA - Abdullahi Hassan, Ndanusa; Karunakaran, Rohini; Abdulmumin, Suleiman (International Journal of Pharmacy and Pharmaceutical Sciences, 2019)
Consumption of fruits and vegetables fight against oxidative damage by inhibiting or reducing free radicals and reactive oxygen species. Mimosa pudica is a perennial herb and belongs to the family Fabaceae. Epidemiological studies have shown that M. pudica contains metabolites such as phenols and flavonoid compounds which possess pharmacological properties such as antidiabetic, antimicrobial, antiulcer, antidepressants and anti-inflammatory. Ecological studies have shown that M. pudica grows in all types of soil which can survive in soil with low nutrient concentration. It usually requires disturbed soil to establish itself. It is commonly seen in the wastelands and along roadsides, which is an ethnomedical plant that may be used in managing various types of disease. Valuable information and literature on M. pudica are analysed and consulted using a different database such as Google Scholar, Google, Science Direct, Web of Science, Academic Journals and Pubmed. This review article summarises the pharmacological properties of M. pudica.